The weight of feathers - McLemore, Anna-Marie (New York Thomas Dunne Books/St. Martin's Griffin, 2015)
Lace Paloma and Cluck Corbeau, from feuding families of traveling performers, fall in love.
Keywords: Love -- Fiction; Families -- Fiction; Vendetta -- Fiction; Performing arts -- Fiction